Therapeutic silencing of miR‐652 restores heart function and attenuates adverse remodeling in a setting of established pathological hypertrophy. Issue 12 (21st August 2014) - Bernardo, Bianca C.; Nguyen, Sally S.; Winbanks, Catherine E.; Gao, Xiao‐Ming; Boey, Esther J. H.; Tham, Yow Keat; Kiriazis, Helen; Ooi, Jenny Y. Y.; Porrello, Enzo R.; Igoor, Sindhu; Thomas, Colleen J.; Gregorevic, Paul; et al.
Abstract : Expression of microRNA‐652 (miR‐652) increases in the diseased heart, decreases in a setting of cardioprotection, and is inversely correlated with heart function. The aim of this study was to assess the therapeutic potential of inhibiting miR‐652 in a mouse model with established pathological hypertrophy and cardiac dysfunction due to pressure overload. Mice were subjected to a sham operation or transverse aortic constriction (TAC) for 4 wk to induce hypertrophy and cardiac dysfunction, followed by administration of a locked nucleic acid (LNA)‐antimiR‐652 (miR‐652 inhibitor) or LNA control. Cardiac function was assessed before and 8 wk post‐treatment. Expression of miR‐652 increased in hearts subjected to TAC compared to sham surgery (2.9‐fold), and this was suppressed by 95% in LNA‐antimiR‐652‐treated TAC mice. Inhibition of miR‐652 improved cardiac function in TAC mice (fractional shortening:29±1% at 4 wk post‐TAC compared to 35±1% post‐treatment) and attenuated cardiac hypertrophy. Improvement in heart function was associated with reduced cardiac fibrosis, less apoptosis and B‐type natriuretic peptide gene expression, and preserved angiogenesis. Mechanistically, we identified Jagged1 (a Notch1 ligand) as a novel direct target of miR‐652. In summary, these studies provide the first evidence that silencing of miR‐652 protects the heart against pathological remodeling and improves heart function.—Bernardo, B. C., Nguyen, S. S., Winbanks, C. E., Gao, X.‐M., Boey, E. J. H., Tham, Y. K., Kiriazis, H., Ooi, J. Y. Y., Porrello, E. R., Igoor, S., Thomas, C. J., Gregorevic, P., Lin, R. C. Y., Du, X.‐J., McMullen, J. R. Therapeutic silencing of miR‐652 restores heart function and attenuates adverse remodeling in a setting of established pathological hypertrophy. FASEB J. 28, 5097–5110 (2014). www.fasebj.org